Trichoderma longibrachiatum (TG1) Enhances Wheat Seedlings Tolerance to Salt Stress and Resistance to Fusarium pseudograminearum - Boamah, Solomon; Zhang, Shuwu; Xu, Bingliang; Li, Tong; Calderón-Urrea, Alejandro (Frontiers in Plant Science, 2021)
Salinity is abiotic stress that inhibits seed germination and suppresses plant growth and root development in a dose-dependent manner. Fusarium pseudograminearum (Fg) is a plant pathogen that causes wheat crown rot. Chemical control methods against Fg are toxic to the environment and resistance has been observed in wheat crops. Therefore, an alternative approach is needed to manage this devastating disease and the effects of salinity. Our research focused on the mycoparasitic mechanisms of Trichoderma longibrachiatum (TG1) on Fg and the induction of defenses in wheat seedlings under salt and Fg stress at physiological, biochemical and molecular levels. The average inhibition rate of TG1 against Fg at day 4 was 23%, 32%, 39%, and 38% respectively in the four NaCl treatments (0, 50, 100, and 150 mM). The mycoparasitic mechanisms of TG1 against Fg were coiling penetration, and wrapping of Fg hyphae. In response to inoculation of TG1 with Fg, significant upregulation of cell wall degrading enzymes (CWDEs) was observed. The expression of β-1, 6-glucan synthase (PP4), endochitinase precursor (PH -1), and chitinase (chi18-15) increased by 1.7-fold, 1.9-fold, and 1.3-fold on day 14 compared with day 3. Wheat seedlings with combined TG1+Fg treatments under different NaCl stress levels decreased disease incidence by an average of 52%; increased the superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activity by an average of 29%, 35%, and 20% respectively; and decreased malondialdehyde (MDA) and hydrogen peroxide (H2O2) content by an average of 43% and 44% respectively compared with Fg treated seedlings. The combined TG1+Fg treatment induced the transcription level of plant defense-related genes resulting in an increase in tyrosin-protein kinase (PR2), chitinase class I (CHIA1), and pathogenesis-related protein (PR1-2) by an average of 1.5-fold, 1.7-fold, and 2-fold respectively. However, the expression levels of phenylalanine ammonia-lyase (PAL) decreased 3.8-fold under various NaCl stresses. Our results suggest that TG1 enhances wheat seedling growth and controls wheat crown rot disease by strengthening the plant defense system and upregulating the expression of pathogenesis-related genes under both Fg and salt stress.